Pengungkapan Corporate Social Responsibility Sebagai Pemoderasi Pengaruh Leverage dan Kepemilikan Manajerial Pada Nilai Perusahaan - Ida Ayu Gde Shinta Vidarani; I Gusti Ayu Nyoman Budiasih (Accounting Department, Economic and Business Faculty of Universitas Udayana in collaboration with the Association of Accounting Department of Indonesia, Bali Region, 2020)
This study aims to determine and obtain empirical evidence about the effect of leverage and managerial ownership on firm value by disclosing corporate social responsibility as a moderating factor. This research was conducted on mining companies listed on the Indonesia Stock Exchange in 2014-2018. The research sample was selected using the nonprobability sampling method with a purposive sampling technique and obtained 13 mining companies, so the number of observations in the study was 65 observations over 5 years. Data analysis techniques used is Moderated Regression Analysis (MRA). Based on the results of the study, it shows that disclosure of corporate social responsibility as a moderating variable weakens the influence of leverage on firm value, disclosure of corporate social responsibility as a moderating variable that strengthens the effect of managerial ownership on firm value. Keywords: CSR Disclosure; Leverage; Managerial Ownership; Firm Value.